Strategic Management of Tourism Development to Attract Tourist Interest in Tigaras, Simalungun Regency - Sinaga, Sadariahma; Saragih, Hisarma; Sipayung, Tuahman (Jurnal Ilmiah Accusi, 2025)
This study is motivated by the low number of tourist visits to the Tigaras area in Simalungun Regency, despite its significant tourism potential in terms of natural beauty and cultural richness. The main issue lies in the ineffective management strategies implemented by local stakeholders. The aim of this research is to identify the tourism potentials that can be developed, analyze the factors hindering the increase in tourist visits, and formulate appropriate tourism management strategies to attract more visitors. This study employs a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and document analysis. The data were analyzed using the interactive model of Miles and Huberman and the SWOT framework. The results reveal that tourism development in Tigaras faces various challenges, including inadequate infrastructure, limited human resource capacity, weak promotional efforts, and poor coordination among stakeholders. The study concludes that an integrated, participatory, and locally-based management strategy is crucial to transform Tigaras into a competitive and sustainable tourism destination